2015
DOI: 10.1080/08952833.2015.1005945
|View full text |Cite
|
Sign up to set email alerts
|

Peace on Earth/War at Home: The Role of Emotion Regulation in Social Justice Work

Abstract: The present article discusses the role of emotions in translating critical awareness of social inequities into action. Our work is premised on the assumption that emotions play a key role in social justice work by not only fueling capacity for resistance but also hindering ability to resist injustice effectively or even prompting unwitting contribution to oppression. Drawing from the clinical psychology literature, we introduce the concepts of psychological flexibility, emotion regulation, and mindfulness to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 71 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Supervisors and training programs are looking for ways to promote cultural sensitivity, global awareness, and equity (e.g., Allan & Poulsen, ; Falender, Shafranske, & Falicov, ; Hernández & McDowell, ; McGeorge, Carlson, Erickson, & Guttormson, ; Platt & Laszloffy, ; Tohidian & Quek, ; Winston & Piercy, ). Preparation for just practice frequently includes development of emotional reflexivity, person‐of‐the‐therapist work, and strategies for dialogue across differences (Aponte & Kissil, ; Garcia, Košutic, & McDowell, ; Hardy & Bobes, ; McGeorge & Carlson, ; Nixon et al., ; Watts‐Jones, ), as well as attention to nuances of power and meaning in each person's intersecting contextual niche (Addison & Coolhart, ; Falicov, ; George & Stith, ).…”
Section: Equitable Practice Is Good Practicementioning
confidence: 99%
“…Supervisors and training programs are looking for ways to promote cultural sensitivity, global awareness, and equity (e.g., Allan & Poulsen, ; Falender, Shafranske, & Falicov, ; Hernández & McDowell, ; McGeorge, Carlson, Erickson, & Guttormson, ; Platt & Laszloffy, ; Tohidian & Quek, ; Winston & Piercy, ). Preparation for just practice frequently includes development of emotional reflexivity, person‐of‐the‐therapist work, and strategies for dialogue across differences (Aponte & Kissil, ; Garcia, Košutic, & McDowell, ; Hardy & Bobes, ; McGeorge & Carlson, ; Nixon et al., ; Watts‐Jones, ), as well as attention to nuances of power and meaning in each person's intersecting contextual niche (Addison & Coolhart, ; Falicov, ; George & Stith, ).…”
Section: Equitable Practice Is Good Practicementioning
confidence: 99%
“…Our findings highlight the importance of developing emotional awareness in social justice related work (Garcia et al, 2015). As our embodiment grew, our bodies sometimes told us where to look, and we determined that tending to our own experience was important.…”
Section: Noticing and Attending To The Felt Experience Of Witnessing ...mentioning
confidence: 64%
“…After observing this session we discussed our shared belief that the female partner was owed attunement and the third author, The third author shared, "I guess this is hitting buttons for me, too, because that was definitely something I really wanted when I was in couples therapy; it felt like our therapist overfocused on why I was "putting up with" the behaviors from my partner rather than [the therapist] interrupting and exploring his behaviors that were emotionally abusive." As suggested by Garcia et al (2015), we found that awareness of our emotion around power enabled us to both avoid reactive responses or blindness to otherwise taken-for-granted power processes and to consider how best to appropriately and effectively take action.…”
Section: Noticing and Attending To The Felt Experience Of Witnessing ...mentioning
confidence: 73%
“…According to Bandura'ssocial learning theory, attitudes are learned through experiences and these experiences are largely shaped by being influenced by the judgments and thoughts of parents during childhood (Ozyurek, 2006;Ozcan & Ozer, 2018). Attitudes, which can also be defined as the positive or negative evaluation of individuals, objects, or events, greatly contribute to the formation of individuals' behaviors and emotional distances (Card, 2005;Gerrig & Zimbardo 2014;Garcia, 2015). For this reason, they have an important role in adjusting the emotional distance between people in social relations (Büyükdag et al, 2019).…”
Section: Introductionmentioning
confidence: 99%